COGNITIVE STYLE PADA NIAT MENGGUNAKAN MEDIA JEJARING SOSIAL “FACEBOOK” (Fokus Ekonomi, 2011)
The purpose of study examine the influence of cognitive style (perceived usefulness and perceived ease of use) on attitude and intention to use Facebook. This research used the Technology Acceptance Model (TAM) as the framework. This research conducted by survey of 105 university student in Purwokerto. Data were analyzed by Partial Least Square (PLS) to investigate the research model. This research used non probability sampling method and convenience sampling technique to collect data. The result found that the perceived ease of use  and perceived usefulness significantly influenced attitude toward using Facebook. Perceived usefulness and attitude significantly influenced intention to use Facebook but perceived ease of use did not significantly influence intention to use Facebook. For next research it is supposed to use large respondents and to add external variables such:self efficacyanxiety, accessibility, experience and psychology factors